D1 NC Symposium manufacturing and evaluation of Kraft propellant lopez.pdf - Gill, Philip (Cranfield University, 2023)
Manufacturing and Evaluation of Kraft AFP001 Propellant Lucas Lopez, Mo Elalem U.S. Army ARDEC Picatinny Arsenal, NJ 07806 USA
Keywords: 'nitrocellulose'